(untitled) (Research, Society and Development, 2022)
The investigation of gastrointestinal parasites in primates kept in captivity is important for the management of these animals and for human health, since many of their parasites cause zoonoses. The aim of this study was to evaluate gastrointestinal parasitism in primates kept in captivity at a Wildlife Animal Screening Center in Bahia, Brazil. 135 stool samples from 45 primates were analyzed using the Direct method and the Hoffman method, three times, with an interval of fifteen days. Infections by protozoa were verified, being mild for Balantidium sp. and Entamoeba sp. and moderate for Cystoisospora sp., the latter had the highest sample prevalence among all the parasites found (91.11%). The presence of helminths of Ancylostoma sp. and Strongyloides sp. was recorded. Infection by gastrointestinal parasites in captive primates is frequent. With the results of the present work, it is concluded that periodic parasitological evaluations are necessary for better sanitary management of these animals.